Degree of differentiation of cutaneous squamous cell carcinoma: a comparison between a Swedish cohort of organ transplant recipients and immunocompetent patients - Caroline Stenman; Helena Gonzalez; Martin Gillstedt; Göran Dellgren; Bengt Hasséus; Erik Holmberg; Helena Rexius; Jenny Öhman; John Paoli (Mattioli1885, 2018)
Background: Organ transplant recipients (OTRs) have a very high risk of developing cutaneous squamous cell carcinoma (cSCC). Immunosuppressed OTRs may have a higher proportion of poorly differentiated cSCC than non-OTRs. Objectives: The aim of this study was to investigate the degree of differentiation of cSCCs in OTRs compared with immunocompetent individuals. Patients/Methods: Data from the Swedish Cancer Registry were crosschecked with data from the Transplant registry of the Transplant Institute at Sahlgrenska University Hospital in Gothenburg, Sweden. All OTRs with a diagnosis of cSCC, basosquamous carcinoma, and/or cSCC in situ established at the Department of Dermatology, Sahlgrenska University Hospital, during 2002-2015 were included. The control group consisted of non-OTRs with the same diagnoses during the same time period. Results: During 2002-2015, 82 OTRs diagnosed with 515 tumors and 883 non-OTRs with 1,247 tumors were included. OTRs developed 0.47 tumors/year vs 0.10 tumors/year for non-OTRs, but no significant differences were observed in the degree of tumor differentiation of invasive cSCCs between OTRs and non-OTRs (P = 0.4). The distribution of poorly, moderately, and well-differentiated invasive cSCCs among OTRs and non-OTRs were 8.5% vs 12.5%, 22.1% vs 29.9%, and 69.4% vs 57.6%, respectively. Conclusions: OTRs do not develop a higher proportion of poorly differentiated cSCCs than non-OTRs.